North American Urban History: The Everyday Politics and Spatial Logics of Metropolitan Life - Sies, Mary (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2003)
At the start of the twenty-first century, North American urban history is flourishing. Compared to twenty-five years ago, the field has become more interdisciplinary and intellectually invigorating. Scholars are publishing increasingly sophisticated efforts to understand how the city as space intersects the urbanization process, as well as studies that recognize the full complexity of experiences for different metropolitan cohorts. A burgeoning literature connects the everyday cultural experiences of urban North Americans with larger social processes and issues of historical analysis. Such a rapidly evolving field defies attempts to summarize the state of its scholarship. This essay will therefore confine itself to a survey of five themes of recent scholarship on the urban history of Canada and the United States: social class and the city, housing studies, urban life and politics, city-suburb relationships, and race relations and the metropolis. These diverse bodies of literature challenge our common wisdom about how cities and suburbs work and inspire urbanists to approach their topics with fresh eyes, an interdisciplinary purview, and an open mind.